ANALISIS STRATEGI PENGEMBANGAN KSPPS USAHA MULYA PONDOK INDAH DENGAN METODE BUSINESS MODEL CANVAS - Amatya Febri Fara Dila, (2023)
The development of Islamic finance in Indonesia cannot be separated from the growth of Islamic cooperatives which has continued to increase from 1992 to the present. Along with the growth of cooperatives, competition between cooperatives cannot be avoided, it is necessary to have business strategies to be able to compete by maintaining the growth of cooperatives through improving the quality of services and products of Islamic cooperatives through the canvas business model. So the purpose of this study was to find out the application of the canvas business model and provide recommendations for alternative strategies for KSPPS Usaha Mulya Pondok Indah through the canvas business model. This research is qualitative in nature with an analysis approach to the business model canvas and the SWOT matrix. The research was conducted at the Pondok Indah Mulya Business Savings and Loans and Sharia Financing Cooperative (KSPPS). Based on the results of the study, it shows that KSPPS Usaha Mulya Pondok Indah is in a growth and build business condition based on the basis of data processing from the SWOT matrix which results in a cooperative position in quadrant I and is a profitable position and still has many opportunities that can be explored in the business development process. The right strategy for sharia cooperatives in this study is a growth-oriented strategy or is said to be a strategy that focuses on maximizing opportunities and existing internal strengths and improvements.